The Association Between Corporate Social Responsibility And Corporate Financial Performance (Issues in Social and Environmental Accounting (ISEA), 2014)
The objectives of this study is to investigate the association between CSR and Corporate Financial Performance (CFP). This study investigates 800 firms listed on Indonesian Stock Exchange in 2010 - 2012. Financial performance is measured by accounting-based approach and stock-market-based approach. While, CSR practices is measured by Corporate Social Disclosure Index (CSRDI). Thus, the association was analyzed under multivariate linear regression by considering time difference. Firm size, growth, and risk are included as control variables. This study finds: (1) CSR provides positive impact on the financial performance until one next period; (2) financial performance measured by ROA influence positively CSR only the next two years; (3) there is significant positive relationship between firm size and CSR. The paper has implications in enhancing the understanding of company performance through understanding the association between CSR and CFP.This may increase the understanding of the association between CSR and CFP. The findings of this study contribute to the literature and regulator on CSR.